Comparison of the Effectiveness of the Gottman Couples Therapy Method and the Cognitive-Behavioral Method on Marital Intimacy Among Students of Islamic Azad University, Hamedan Branch - Saravi, Abdolreza; jadidyan , Ahmad Ali; Nejatian Tanha , Arezo (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
This study aimed to compare the effectiveness of Gottman couples therapy and cognitive-behavioral couples therapy on marital intimacy among students of Islamic Azad University, Hamedan Branch. Methods and Materials: The study employed a quasi-experimental pretest-posttest design with a control group. The statistical population included all married students of Islamic Azad University, Hamedan Branch, in the academic year 2023-2024. Using convenience sampling, 45 participants were selected and randomly assigned to three groups: Gottman couples therapy (15 participants), cognitive-behavioral couples therapy (15 participants), and a control group (15 participants). The intervention consisted of 10 sessions of 90 minutes for the Gottman method and 8 sessions of 90 minutes for the cognitive-behavioral method. The control group did not receive any intervention. Marital intimacy was assessed before and after the intervention using Waring’s Marital Intimacy Questionnaire. Data analysis was conducted using SPSS-24, employing multivariate analysis of covariance (MANCOVA) and one-way analysis of variance (ANOVA) to compare the effectiveness of the interventions. Findings: The results showed that both Gottman couples therapy and cognitive-behavioral couples therapy significantly improved marital intimacy compared to the control group. The mean marital intimacy scores in the Gottman therapy group increased from 107.05 (SD = 6.99) in the pretest to 116.61 (SD = 6.521) in the posttest, while in the cognitive-behavioral therapy group, scores increased from 104.42 (SD = 6.539) to 114.8 (SD = 5.668). MANCOVA results confirmed a statistically significant difference between the two interventions (p < 0.05), with the cognitive-behavioral approach demonstrating a slightly higher effect size. Conclusion: Both Gottman couples therapy and cognitive-behavioral couples therapy effectively enhanced marital intimacy, with the cognitive-behavioral approach showing slightly greater efficacy. These findings highlight the importance of selecting a therapy tailored to the specific needs of couples. Future research should explore the long-term effects of these interventions and examine their applicability in diverse populations.